Constructing civil society in Japan - Hasegawa, Koichi (Trans Pacific Press, 2004)
Based on four major case studies, this book offers an overview of contemporary Japan's changing attitudes and policies regarding environmental issues. Beginning in the 1970s, the author traces how the rapid growth of environmental politics and actions contributed to the development of a vibrant civil society.